Parámetros Reproductivos del Ganado Nellore en la Selva Central del Perú (2000-2007) - Chirinos Peinado, Doris Maritza (2017)
The aim of this study was to assess the status of major reproductive parameters of Nellore cattle reared in the central tropics of Peru. Reproductive data of 63 cows that had three consecutive calvings between 2000 to 2007 was used. The variables were age at first conception, age at first calving, interval between the first, second and third calving, open days between second and third calving, and calf birth weight in the first four parturitions. Age at first conception was 30.7 ± 6.0 months (range: 17.7 to 42.9 months), age at first calving was 40.2 ± 6.0 months (range: 27.2 to 52.4 months), calving interval was 434.1 ± 58.6 days (range: 317 to 540 days), open days was 179.8 ± 55.5 days (range: 90-292 days) and body weight at birth was 27.0 ± 4.9 kg (range: 20-40 kg).